‘El Palmeral’ apartments in Aguadulce by Fernando Cassinello - García-Sánchez, José-Francisco; Centellas-Soler, Miguel (Revista de la Construcción. Journal of Construction, 2020)
’El Palmeral’ apartments (1968-1970) located in Aguadulce, a tourist town in Almería, in the Andalusian region of southern Spain are the best work by the architect Fernando Cassinello (Almería, 1928-Madrid, 1975). The urban planning regulations of the development, which required the ground floor to be diaphanous, made possible the original solution of the three great reduced arches with the upper structure of porticos on each block. Hence, the apartments rest on six large arches, producing an image similar to that of an inhabited bridge. Fernando Cassinello, in his dual capacity as professor at the School of Architecture in Madrid and researcher at the Eduardo Torroja Institute of Construction Sciences (IETcc), always positioned himself in the median that unites Architecture and Engineering. In some of his works, an infrastructural derivative can be appreciated. Therein lays the interest of his architectural work. He was able to introduce singular structural aspects, even in private housing projects, both single family and collective. This could be in the way his buildings were related to the ground, or the way he dealt with stairs, which have so often been excluded from the built volume, and which served functions beyond facilitating vertical movement.